International Network-to-Network: Annotated Bibliography - Middendorf, B. Jan; Carnes, Rebekah (Feed the Future Innovation Lab for Collaborative Research on Sustainable Intensification, Kansas State University, 2020)
Acknowledgements: This material is based upon work supported by the National Science Foundation under Grant No. 1842111 - International Network-to-Network (N2N) Stakeholder Collaboration: Solutions to Accelerate Research, Leverage Resources, and Maximize Synergies. Disclaimer: Any opinions, findings, and conclusions or recommendations expressed in this material are those of the author(s) and do not necessarily reflect the views of the National Science Foundation. Readers should be aware that Internet Web sites offered as citations and/or sources for further information may have changed or disappeared between the time this was written and when it is read.
Keywords: International; Collaboration; Network-to-Network; Team Science